THE ROLE OF MODERN UZBEK LITERARY LANGUAGE CLASSES IN DEVELOPING COMMUNICATIVE COMPETENCE - Umida Abdurasulova (Innovate Conferences, 2026)
This article provides a scientific and theoretical analysis of the role of modern Uzbek literary language classes in developing communicative competence among students majoring in English. The study examines the concept of communicative competence, its main structural components, and highlights the impact of speech skills and abilities formed in the mother tongue on the process of foreign language acquisition.
Keywords: Communicative competence, Uzbek literary language, speech culture, English language major, sociocultural competence, game, task, modern education.